Lake Atitlán, Guatemala: "The Possibility of a Shared World” (Alternautas, 2022)
Conflicts around development issues are increasingly focused on water. These conflicts tend to intertwine a struggle over whether water should be treated as a commodity with struggles over how its management should be configured, and by whom (Castro 2008). Latin America has emerged as a particularly relevant region for these debates (Ávila-Garcia 2016). This article presents the case of Lake Atitlán, in the Sololá department of Guatemala, where long-standing conflicts and divergent imaginaries have made it difficult to create consensus about how to solve an ecological problem. The article is based on four months (April to July 2016) of ethnographic fieldwork, in three towns and one village on the shores of the lake. Many names and other identifying details are left out, due to safety concerns.